Why Abusive Supervision Impacts Employee OCB and CWB: A Meta-Analytic Review of Competing Mediating Mechanisms - Zhang, Yucheng; Liu, Xin; Xu, Shan; Yang, Liu-Qin; Bednall, Timothy C. (Journal of Management, 2019)
Studies on abusive supervision have adopted justice and resource perspectives to explain its effects on employee organizational citizenship behavior (OCB) and counterproductive work behavior (CWB). However, these studies have not provided a comprehensive account of why abusive supervision affects OCB and CWB and which of these two mediating mechanisms matters more. To address these questions, we conducted two studies using meta-analytic structural equation modeling. In the main study, we analyzed 427 primary studies that incorporated 973 independent correlations ( N = 336,236). The results showed that both organizational justice (the justice lens) and work stress (the resource lens) mediated the influence of abusive supervision on OCB and CWB. Furthermore, organizational justice accounted for a greater proportion of abusive supervision’s effect on OCB than did work stress, whereas work stress accounted for a greater proportion of abusive supervision’s effect on CWB than did organizational justice. Finally, between-study moderation analyses showed that the effect of abusive supervision on CWB was stronger in masculine cultures than in feminine cultures. The supplementary study incorporated effect sizes from six existing meta-analyses ( N = 151,381) and largely replicated the main study’s findings.